# If f(x) = 3x, g(x) = x^2 -1, then find f(g(3))(HINT:The answer to

this question should be a number not another function.)

g(3) = 9 - 1 = 8, and f(g(3)) = f(8) = 24

## To find the value of f(g(3)), we need to substitute the value of g(3) into the function f(x).

First, let's calculate g(3). Plug in the value of x=3 into the function g(x) = x^2 - 1:

g(3) = 3^2 - 1 = 9 - 1 = 8

Now that we have the value of g(3) as 8, we can substitute it into the function f(x) = 3x:

f(g(3)) = f(8) = 3 * 8 = 24

Therefore, the value of f(g(3)) is 24.